SYSTEMATIC LITERATURE REVIEW: EFEKTIVITAS DISCOVERY LEARNING TERHADAP HASIL BELAJAR IPS SISWA KELAS lV SEKOLAH DASAR - Yulinda; Syahira; Wiky Santia Witama; Wulandari; Susi Ratna Sari; Zahra Maharani Safitri (STKIP Subang, 2026)
This study aims to analyze the effectiveness of the Discovery Learning model on the learning outcomes of fourth-grade elementary school students through the Systematic Literature Review (SLR) method. This study is motivated by the low level of active student participation in the social studies learning process, so a learning model that can improve student understanding and learning outcomes is needed. The method used in this study is a Systematic Literature Review by collecting and analyzing scientific articles relevant to the research topic. Data were obtained through the Google Scholar database using the Publish or Perish application with the keywords